The effects of joining a strategic alliance group on airline efficiency, productivity and profitability : a thesis presented in partial fulfilment of the requirements for the degree of Doctorate of Philosophy in Aviation at Massey University, Palmerston North, New Zealand - Lin, Bo (Massey University, 2013)
A global airline strategic alliance group is a larger cooperation formed by several airlines in order to obtain strategic advantages in their business operations. Nowadays, airline strategic alliance groups have become an important sector of the airline industry and also tend to have dominance in airline business. Airlines want join a strategic alliance group in order expand their business and reduce their costs – and expect to. However, the true benefits of the effects of a strategic alliance group still remain unclear. Little research has been done on how airline alliance strategic groups affect changes in airline performance. This study adopts three different empirical quantitative analyses to reveal the effects of a strategic alliance group on airline performance. The performance indicators included airline technical efficiency, productivity and profitability. The research focuses on 20 international airlines during the 1995–2005 periods from two major categories: allied airlines, which included three global airline strategic alliance groups, and non-allied airlines. The research used data envelopment analysis and stochastic frontier analysis to assess the airlines? technical efficiency, while panel regression analysis for airline productivity and profitability. The results suggest that joining an airline strategic alliance group generally will have positive effects on its member airlines? technical efficiency, productivity and profitability. However, the results are not statistically significant. This implies that the effects of an airline alliance group are practically unimportant to the airline performance, particularly during the study period. Thus this research reveals that airlines joining the alliance group may not necessarily achieve significant improvements in their performance. During the pre-maturity stage of the alliance group, joining an alliance does not necessary bring positive effects to the airlines? performance. Secondly, the research suggests that alliance group membership numbers do not always have a positive impact on the airline performance, so alliance groups should consider their size. For newly entering airlines, choosing a relatively smaller alliance group can reduce the entry cost. Moreover, the research also shows that there is a minimum membership duration before an airline can receive alliance group membership benefits. It implies that airlines who seek to join the alliance group as a quick solution will not have their expectations met. Further, the research has confirmed the strong year effect existing in the airline industry, which further suggested that alliance group effects are limited and should not be considered as a universal solution.
Keywords: Strategic alliances (Business); Airlines; Economic aspects; Research Subject Categories::SOCIAL SCIENCES::Business and economics::Business studies